Analisis Pengaruh Variabel-Variabel dalam Perekonomian Terbuka terhadap Pertumbuhan Produk Domestik Regional Bruto (PDRB) Provinsi Bali (Studi Kasus pada Sub Sektor Barang dari Kayu) - I Gusti Ayu Athina Wulandari; A.A. Gede Agung Parameswara (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2018)
Industry of wood handycraft is one of sub sector export oriented industry where the product becomes a superior export commodity. Nevertheless, the growth of GDP are fluctuated based on times series data from 2008-2016. This research using multiple regression analysis. The result shows that in simultan effect ,inflation, US exchange, and export value have a significant effect to the growth of GDP sub sector wood handycrat industry. In partial effect, inflation and US exchange have a positive and signifficant effect while the export value have no significant effect to the growth of GDP sub sector wood handycraft industry.